Do New Technologies Improve Translation Pedagogy? - Varela-Salinas, María José (My University, 2019)
This contribution wants to add to the discussion if technology supports translator training and where its advantages and boundaries lie. It is by no means exhaustive; rather it is intended to serve to highlight the diversity of possible applications using a pedagogic focus.
Keywords: Pedagogía; translation; translator training; technology; pedagogy; translation memory (TM); machine translation (MT); glossary; Sketch Engine; CAT tools